Women Labor Force Participation and Total Fertility in Four Selected Asean Countries - Surianti, Mat Fiah (2011)
The relationship between female labor force participation rate (WLFPR) and fertility rates (TFR) are often a topic of discussion at present. Many studies have been conducted to find the true relationship between these two variables. Female labor force participation rate and fertility rate are among the most important indicators of a country's economic development. The objective of this study was to find the real relationship between these indicators for the four selected ASEAN countries, namely Malaysia, Indonesia, Philippines and Thailand. The selection of countries is based on the similarity of demographic patterns, particularly the rate of population, trade, GNP growth, and unemployment rates. Due to the fact ASEAN member countries are countries in a region, therefore any changes in terms of policy implementation made by a neighboring country do give impact to another. Besides reviewing the trends of WLFPR and fertility rates, using the 28 years of time series data, this study uses Augmented Dickey Fuller test (ADF) to test the stationarity of variables, Johansen test to observe cointegration and Granger Causality tests to find out the causal relationship between the variables. The results show that female participation rate has a negative relationship with total fertility rates in all of the selected countries. In view of the fact that increasing in WLFPR will reduce TFR, each government should be more cautious in making policies regarding the participating of women, in the labor force as it has negative consequences on population growth and this can negate economic growth in the long-run.